Gas exchange and leaf aging in an evergreen oak: causes and consequences for leaf carbon balance and canopy respiration - Rodriguez-Calcerrada, Jesus; Limousin, Jean-Marc; Martin-StPaul, Nicolas K; Jaeger, Carsten; Rambal, Serge (Tree Physiology, 2012)
Leaves of Mediterranean evergreens experience large variations in gas exchange rates over their life span due to aging and seasonally changing environmental conditions. Accounting for the changing respiratory physiology of leaves over time will help improve estimations of leaf and whole-plant carbon balances. Here we examined seasonal variations in light-saturated net CO2 assimilation (Amax), dark respiration (Rd) and the proportional change in Rd per 10 °C change in temperature (Q10 of Rd) in previous-year (PY) and current-year (CY) leaves of the broadleaved evergreen tree Quercus ilex L. Amax and Rd were lower in PY than in CY leaves. Differences in nitrogen between cohorts only partly explained such differences, and rates of Amax and Rd expressed per unit of leaf nitrogen were still significantly different between cohorts. The decline in Amax in PY leaves did not result in the depletion of total non-structural carbohydrates, whose concentration was in fact higher in PY than CY leaves. Leaf-level carbon balance modeled from gas exchange data was positive at all ages. Q10 of Rd did not differ significantly between leaf cohorts; however, failure to account for distinct Rd between cohorts misestimated canopy leaf respiration by 13% across dates when scaling up leaf measurements to the canopy. In conclusion, the decline in Amax in old leaves that are close to or exceed their mean life span does not limit the availability of carbohydrates, which are probably needed to sustain new growth, as well as Rd and nutrient resorption during senescence. Accounting for leaf age as a source of variation of Rd improves the estimation of foliar respiratory carbon release at the stand scale.
10.1093/treephys/tps020
Keywords: carbon budget; ecosystem respiration; leaf life span; resource remobilization; soluble sugars; temperature sensitivity

Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks - Sanz-Pérez, V; Castro-Diez, P; Valladares, F (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.
Keywords: Global warming; Lipids; Phenology; Quercus faginea; Quercus ilex; soluble sugars; starch; wood anatomy

Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks - Sanz-Pérez, V.; Castro-Díez, P.; Valladares, F. (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Global warming; Lipids; Phenology; Quercus faginea; Quercus ilex; soluble sugars; starch; wood anatomy